Taxing crypto-asset transactions: Foundations for a globally coordinated approach - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2024)
With the total market capitalisation of crypto-assets amounting to trillions of US dollars, it isclear that crypto taxation needs to be taken seriously by both tax administrations and taxpayers.Over the past few years, numerous tax administrations around the world have devoted resourcesto crypto taxation, as evidenced by the substantial amount of guidance that has been madeavailable to taxpayers. International organisations such as the Organisation for EconomicCo-operation and Development (OECD) and the United Nations have also released publicationson crypto taxation. Despite all these domestic and international efforts to provide guidance oncrypto taxation, there remains considerable uncertainty as to the tax treatment of crypto-assetsand transactions. In the first chapter of this excellent book by Shaun Parsons, the current situationis summed up concisely, highlighting “global tax confusion over the treatment of crypto-assets”,absence of a globally coordinated approach, and “lack of consensus about what those taxconsequences should be”.